A discussion on `Domain formation and phase transitions in the wurtzite‐based heterovalent ternaries: a Landau theory analysis'. Issue 3 (23rd March 2021) - Quayle, Paul C.; Breternitz, Joachim
Abstract : A scientific exchange on an earlier paper [Quayle (2020). Acta Cryst. A76, 410–420] has led to the clarification of some of the points. Abstract : Heterovalent ternary nitrides are considered one of the promising classes of materials for photovoltaics, combining attractive physical properties with low toxicity and element abundance. One of the front‐runner systems under consideration is ZnSnN2 . Although it is nominally a ternary compound, no clear crystallographic evidence for cation ordering has been observed so far. An attempt to elucidate this discrepancy [Quayle (2020). Acta Cryst. A76, 410–420] was the trigger for an intensive discussion between the authors, and an agreement was reached to elaborate on some points in order to set things in perspective. Rather than using a conventional comment–answer scheme, this is published in the form of a joint discussion to celebrate constructive criticism and collegiality.